CamRegBase: a gene regulation database for the biofuel crop, Camelina sativa. (11th December 2020) - Gomez-Cano, Fabio; Carey, Lisa; Lucas, Kevin; García Navarrete, Tatiana; Mukundi, Eric; Lundback, Steve; Schnell, Danny; Grotewold, Erich
Abstract: Camelina is an annual oilseed plant from the Brassicaceae family that is gaining momentum as a biofuel winter cover crop. However, a significant limitation in further enhancing its utility as a producer of oils that can be used as biofuels, jet fuels or bio-based products is the absence of a repository for all the gene expression and regulatory information that is being rapidly generated by the community. Here, we provide CamRegBase (https://camregbase.org/ ) as a one-stop resource to access Camelina information on gene expression and co-expression, transcription factors, lipid associated genes and genome-wide orthologs in the close-relative reference plant Arabidopsis . We envision this as a resource of curated information for users, as well as a repository of new gene regulation information.